REVIEW ON COPING STRATEGIES AMONG CAREGIVERS OF PEOPLE WITH SCHIZOPHRENIA - Tengku Mohd Saifuddin Tengku Kamarulbahri; Muna Hamiza Asiff; Muhammad Adib Baharom, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Individuals diagnosed with Schizophrenia often experience compromised social functioning, contributing not only to the distress of the affected individuals but also imposing a considerable burden on their caregivers. Consequently, it becomes imperative to employ effective coping strategies to alleviate the stress experienced by those caring for individuals with Schizophrenia stemming from diverse stressors. However, there is a scarcity of research examining the factors associated with these coping strategies. This review aims to investigate the coping mechanisms employed by caregivers of individuals diagnosed with Schizophrenia, elucidating their associated factors, and examining the psychological distress experienced by caregivers. Findings from the review reveal a discernible relationship between psychological distress and coping styles. This review showed a correlation between coping styles and demographic factors like education level influencing coping mechanisms. The findings highlight the importance of tailored interventions to support caregivers, enhance coping strategies, and mitigate psychological distress, ultimately fostering improved overall mental health outcomes for both caregivers and individuals with Schizophrenia. Consequently, there is a pressing need for further research to comprehensively comprehend how coping strategies can effectively support caregivers of individuals with Schizophrenia, contributing to a more holistic approach to patient treatment.